2012
DOI: 10.3390/cancers4020490
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Mediated Immune Responses Induced in ret Transgenic Mouse Model of Malignant Melanoma

Abstract: Poor response of human malignant melanoma to currently available treatments requires a development of innovative therapeutic strategies. Their evaluation should be based on animal models that resemble human melanoma with respect to genetics, histopathology and clinical features. Here we used a transgenic mouse model of spontaneous skin melanoma, in which the ret transgene is expressed in melanocytes under the control of metallothionein-I promoter. After a short latency, around 25% mice develop macroscopic skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…21,22 In addition, primary skin melanomas and metastases in lymph nodes (LNs) and distant organs of transgenic mice express similar MAAs to those expressed in human melanoma and B16 tumors (such as gp100, Tyr, TRP-1 and TRP-2). 22,23 Our data suggest that immunotherapy with DCs-based antitumor vaccine can significantly improve the survival of tumorbearing ret transgenic mice. Analyzing the mechanism of such effect, we observed elevated frequencies of central and effector memory T-cell subsets in vaccinated mice.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…21,22 In addition, primary skin melanomas and metastases in lymph nodes (LNs) and distant organs of transgenic mice express similar MAAs to those expressed in human melanoma and B16 tumors (such as gp100, Tyr, TRP-1 and TRP-2). 22,23 Our data suggest that immunotherapy with DCs-based antitumor vaccine can significantly improve the survival of tumorbearing ret transgenic mice. Analyzing the mechanism of such effect, we observed elevated frequencies of central and effector memory T-cell subsets in vaccinated mice.…”
Section: Introductionmentioning
confidence: 97%
“…36,37 Previous studies performed on ret transgenic tumor-bearing mice demonstrated that targeting of MDSC by the phosphodiesterase-5 inhibitor sildenafil or ultra-low dose paclitaxel significantly increased animal survival associated with the restoration of antitumor T-cell functions. 23,38 On the other side, it has been reported that, T cells may promote melanoma progression in this mouse model by favoring protumoral properties of tumor-infiltrating myeloid cells that further inhibit functions of immune effector cells. 39 In this study, we found no statistically significant changes in MDSC frequencies in melanoma lesions and lymphoid organ upon vaccination with modified DCs, indicating that this immunization does not display side effects dealing with the MDSC accumulation.…”
Section: Studying Cd4mentioning
confidence: 99%
“…While mutations in the RET oncogene are not very frequent in human melanoma, they result in activation of common oncogenic downstream signaling pathways, such as MEK kinases and p38 MAPK (12). In addition, Ret-melanoma cells express typical melanoma antigenic markers including TRP2, gp100 and TRP1 (17). The transplantable model we established recapitulates the pathologic multistep process of metastasis, including a relatively high penetrance of brain macrometastases.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic mouse lines with either overactivated RET mutations or overexpression of wild-type RET develop melanosis and benign melanocytic lesions that eventually progress to metastatic melanoma (Abschuetz et al, 2012;Kato et al, 1998Kato et al, , 2000Ohshima et al, 2010;Umansky & Sevko, 2013). It has been shown that the progression from benign lesions to melanomas corresponds with increasing levels of RET expression and its activation in tumors from these mouse models (Kato et al, 1998).…”
Section: The Gdnf-ret Axis and Pnimentioning
confidence: 98%